The Functional Impact of Alternative Splicing on the Survival Prognosis of Triple-Negative Breast Cancer - Wu, Sijia; Wang, Jiachen; Zhu, Xinchao; Chyr, Jacqueline; Zhou, Xiaobo; Wu, Xiaoming; Huang, Liyu (Frontiers in Genetics, 2021)
Purpose: Triple-negative breast cancer (TNBC) is a type of breast cancer showing high recurrence ratio and low survival probability which requires novel actionable molecular targets. Then the involvement of alternative splicing (AS) in TNBC promoted us to study the potential roles of AS events in the survival prognosis of TNBC patients. Methods: 150 TNBC patients from TCGA were involved in this work. To study the effects of AS in the recurrence free survival (RFS) prognosis of TNBC, we performed the analyses as follows. First, univariate cox regression model was applied to identify RFS-related AS events. Their host genes were analyzed by metascape to discover the potential functions and involved pathways. Next, LASSO method was used to select the most informative RFS-related AS events to constitute an AS risk factor for RFS prognosis, which was evaluated by Kaplan–Meier (KM) and receiver operating characteristic (ROC) curves in all the data and also different clinical subgroups. Further, we analyzed the relationships between splicing factors (SFs) and these RFS-related AS events, to seek the possibility that SFs regulated AS events to influence RFS. Then we evaluated the potential of these RFS-related AS events in the overall survival (OS) prognosis from all the above aspects. Results: We identified a total of 546 RFS-related AS events, which were enriched in some splicing and TNBC-associated pathways. Among them, seven RFS-related events were integrated into a risk factor, exhibiting satisfactory RFS prognosis alone and even better performance when combined with clinical TNM stages. Further, the correlation analysis between SFs and the seven AS events revealed the hypotheses that SRPK3 might up-regulate PCYT2_44231_AA to have an effect on RFS prognosis, and that three other SFs may work together to down-regulate FLAD1_7874_RI to influence RFS prognosis. In addition, the seven RFS-related AS events were validated to be promising in the OS prognosis of TNBC as well. Conclusions: The abnormal alternative splicing events regulated by splicing factors may act as a kind of biomarkers for the survival prognosis of TNBC.